Hemophagocytic lymphohistiocytosis secondary to virus infection and followed by lupus nephritis recurrence in a renal transplantation pediatric recipient: a case report - Jiyuan Li; Chen Gao; Xuejing Zhu; Danyi Yang; Wendan Mao; Hengchang Yao; Mingyang Deng; Liang Tan; Helong Dai; Xubiao Xie; Longkai Peng; Fenghua Peng (BMC Nephrology, 2023)
Abstract Background Hemophagocytic lymphohistiocytosis (HLH) is a rare and life-threatening disorder characterized by systemic inflammation and organ failure as a result of dysregulated immune cell activation. HLH can be induced by a variety of factors including infection, tumours and autoimmune disease and can also occur in patients following solid organ transplantation. Occurrence of HLH and lupus nephritis (LN) successively within a short period of time after renal transplantation is uncommon. Case presentation We described an 11-year-old female post-transplant patient who presented with hemocytopenia, fever, elevated serum ferritin, splenomegaly, hyperlipidemia, and hypofibrinemia, and was clinically diagnosed with HLH. After comprehensive treatment with corticosteroids, intravenous immunoglobulin (IVIG), and reducing immunosuppressants, her condition improved, but then hematuria ensued. The transplant kidney biopsy showed LN. She was treated with hydroxychloroquine and methylprednisolone while intensive immunosuppressive agents were given. She has remained in remission for two years until now. Conclusions The main inducing factors of HLH should be identified as early as possible, and accurate treatment plans should be taken. The long-course IVIG regimen may be one of the effective treatments for virus-induced HLH. After remission of HLH, we need to be alert to the recurrence of autoimmune diseases in patients with underlying diseases, and timely increase immunosuppressants.